Enhanced data envelopment analysis for sustainability assessment: A novel methodology and application to electricity technologies. (12th July 2016) - Galán-Martín, Ángel; Guillén-Gosálbez, Gonzalo; Stamford, Laurence; Azapagic, Adisa
Graphical abstract: Highlights: An enhanced data envelopment analysis tailored to assess sustainability is proposed. The novelty relies on the incorporation of the concept of order of efficiency. Our approach allows ranking alternatives according to sustainability principles. The method provides targets for inefficient alternatives to become more sustainable. The method is applied to assess several electricity generation technologies. Abstract: Quantifying the level of sustainability attained by a system is a challenging task due to the need to consider a wide range of economic, environmental and social aspects simultaneously. This work explores the application of data envelopment analysis (DEA) to evaluate the sustainability 'efficiency' of a system. We propose an enhanced DEA methodology that uses the concept of 'order of efficiency' to compare and rank alternatives according to the extent to which they adhere to sustainability principles. The capabilities of the proposed approach are illustrated through a sustainability assessment of different technologies for electricity generation in United Kingdom. In addition to screening the alternatives based on sustainability principles, enhanced DEA provides improvement targets for the least sustainable alternatives that, if achieved, would make them more sustainable. The enhanced DEA shows clearly the ultimate distance to sustainability, helping industry and policy makers to improve the efficiency of technologies, products and policies.